Analysis of Archival Internships Conducted in Information Institutions in Türkiye within the Scope of Mentoring: An Evaluation from the Perspective of Interns - Uran, Serhat; Çiçek, Niyazi (Information World, 2025)
It is well known that in fields where theory and practice go hand in hand, there is a need for methods that enable theoretical knowledge to be reflected in practice. Internships are one of the methods that have emerged to meet this need. The effective design of internships is important for students to gain experience in a field that may become their future profession. However, it is understood from both field observations and feedback from students that internships at some archival institutions are not well planned, and therefore interns do not gain sufficient experience in professional practice through real-life cases. This situation indicates that the gains from the internship are insufficient. Mentoring, which has been applied in many fields in recent years as a model that increases work efficiency and develops personal and professional knowledge and skills, is considered to be beneficial for archival internships as well. The purpose of this study is to reveal whether archival internships in Information and Document Management (IDM) departments meet the criteria of mentoring. Within this scope, the work processes of students participating in archival internships were evaluated in terms of mentoring methodology. A quantitative research method was used in the study, and a survey was administered to 361 individuals who had completed archival internships between 2015 and 2019. Student opinions were evaluated to determine the extent to which the internships were consistent with mentoring methodology. When the results were evaluated, it was observed that the mentoring stages could not be fully provided due to reasons such as the lack of an internship program, lack of information, and lack of orientation, and that the satisfaction rates of interns had decreased. The findings indicate that perceptions of mentoring vary depending on the type of institution where the internship is conducted, and that students who intern at institutional archives provide more positive evaluations of the mentoring stages (e.g., for career function, F=2,259; p
Keywords: Archival training; internship; archive internship; mentoring; mentor; mentee